Language Style Found in Guillermo del Toro's Pinocchio Movie (2022) - Meidiana Meidiana; Prihatin Puji Astuti (Journal of Pragmatics Research, 2024)
This research, entitled " Language Style Found in Guillermo del Toro's Pinocchio Movie", aims to analyze the language styles and the factors contributing to the variance in the characters' speech styles within the film. The research employs a qualitative descriptive method, where data was collected through a thorough analysis of the movie, a meticulous examination of the movie script, and the subsequent identification of language styles and factors based on the characters' dialogues. The analysis is framed within Joos's (1967) theory of language styles and Holmes's (2013) theory of language factors. These styles are noticeable based on speaker context, formality, audience, and conversation setting. The research findings highlight the use of five distinct language styles - frozen, formal, consultative, casual, and intimate - in the characters' dialogues. A variety of factors, such as the participants in the conversation, the setting, the subject matter, and the function of the dialogue, influenced these styles. Furthermore, the predominant language style in the movie is casual, comprising fifteen instances, while the frozen style is represented by only one occurrence. This research thus offers valuable insights into the complex interplay between language style and its influencing factors within the realm of film dialogue.